KESIAPAN GURU SEKOLAH DASAR DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN IPS KELAS IV DI SDN 2 KALIMANAH WETAN - Mutiara Hamida Salsabila; Cicih Wiarsih (STKIP Subang, 2024)
The advancement of the educational system to keep pace with the progress of the timeswhether in cultural, societal, knowledge, or technological aspectsrequires changes in Indonesia's curriculum. Therefore, teachers' readiness is key to successfully implementing the curriculum. This study aims to assess the readiness of elementary school teachers in implementing the Merdeka Curriculum specifically for Social Studies in Grade IV at SDN 2 Kalimanah Wetan. The study evaluates teachers' cognitive, physical, psychological, and financial readiness using observation, interviews, and documentation. A qualitative approach with a phenomenological method was used. Data were collected through interviews with the principal, Grade IV teachers, and seven Grade IV students regarding their readiness to implement the Merdeka Curriculum. The findings indicate that Grade IV teachers understand the concepts and principles of the Merdeka Curriculum. This is evidenced by the preparation of teaching modules, Learning Objectives (CP), and Learning Activity Programs (ATP) that align with the characteristics of the Merdeka Curriculum. Social Studies teaching has also implemented differentiated learning.